2014
DOI: 10.1121/1.4837855
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of acoustic streaming in a cylindrical wave guide up to high streaming Reynolds numbers

Abstract: Measurements of streaming velocity are performed by means of Laser Doppler Velocimetry and Particle Image Velociimetry in an experimental apparatus consisting of a cylindrical waveguide having one loudspeaker at each end for high intensity sound levels. The case of high nonlinear Reynolds number ReNL is particularly investigated. The variation of axial streaming velocity with respect to the axial and to the transverse coordinates are compared to available Rayleigh streaming theory. As expected, the measured st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 20 publications
(30 reference statements)
6
28
0
Order By: Relevance
“…Fig. 1(b) shows the distorted streaming pattern (result from the numerical simulation N 2 further described in this paper) in the fast streaming regime, when two new streaming cells are observed in the center of the guide, near the acoustic velocity antinode (z/L = 0) [19,28,29]. Several sources could potentially be responsible for this mutation of streaming pattern: thermal effects were considered [26], as well as nonlinear propagation [29] and it was concluded that inertial effects on acoustic streaming could be the main source [29].…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Fig. 1(b) shows the distorted streaming pattern (result from the numerical simulation N 2 further described in this paper) in the fast streaming regime, when two new streaming cells are observed in the center of the guide, near the acoustic velocity antinode (z/L = 0) [19,28,29]. Several sources could potentially be responsible for this mutation of streaming pattern: thermal effects were considered [26], as well as nonlinear propagation [29] and it was concluded that inertial effects on acoustic streaming could be the main source [29].…”
Section: Introductionmentioning
confidence: 88%
“…The established streaming flow behavior for high acoustic amplitudes (i.e. in the nonlinear regime of streaming) was previously analyzed numerically [19] (with a DNS code) and experimentally [28]: additional streaming cells were observed inside the resonator [29]. Fig.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Laser Doppler Velocimetry and Particle Image Velocimetry provide information about the gas parcel velocity and have been used previously to characterize acoustic streaming [14][15][16][17] or vortex shedding processes [18][19][20], while cold wire anemometry [21] has been used to characterize the nonlinear temperature fluctuations in the vicinity of the stack termination. In this paper, attention is focused on the development of another measurement method allowing to get information about density http://dx.doi.org/10.1016/j.expthermflusci.2015.09.012 0894-1777/Ó 2015 Elsevier Inc. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%